Myasthenia Gravis - rescuing the smile in phonoaudiological rehabilitation - Leico Oda, Adriana; de Magalhães Leal Chiappetta, Ana Lúcia; Martins Medrano, Lígia Maria (O Mundo da Saúde, 2006)
Acquired Autoimmune Myasthenia Gravis is an illness that affects the postsynaptic membrane of the neuromuscular junction. It can affect ocular and bulbar musculature or be generalized. Its main symptoms are: diplopy, unilateral or bilateral ptose, weakness, persistent fatigue, disfony, disartry, disfagy, dyspnea and loss of the facial mimic. Such alterations can make the patient to suffer an impact in her personal, familiar, social and professional life. In this study, we show the introduction of a therapeutic approach directed to expres- sivity by means of smiles and facial mimic, being part of the phonoaudiological work of the Myasthenia Gravis Clinic, in the Research Departmenton Neuromuscular Illnesses of São Paulo’s School of Medicine (UNIFESP-EPM São Paulo). Through the analysis of the stories of the patients, it was possible to study the positive effect of the phonoaudiological treatment in the life of patients with Myasthenia Gravis.